IMPLEMENTASI METODE ROLE PLAY UNTUK MENGEMBANGKAN MAHARAH KALAM - Silfia Kurnia Sari; Ahmad Rifa’i (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2026)
This study aims to describe the implementation of role play method in developing maharah kalam (speaking skill) and student learning motivation at MTsN 7 Blitar. This research uses a qualitative descriptive approach with a case study design. Data were collected through observation, interviews, and documentation involving Arabic language teachers and class VIII students. The results show that the role play method is effective in improving students' speaking skills, indicated by increased fluency, pronunciation accuracy, and confidence in communicating in Arabic. In terms of learning motivation, this method increases student engagement, creates a pleasant learning atmosphere, and encourages more active student participation. The role play method also contributes significantly to students' courage to practice Arabic in everyday situations. The conclusion of this study confirms that the role play method is a relevant and effective strategy to be applied in Arabic language learning, especially in improving maharah kalam and learning motivation at the madrasah tsanawiyah level.